Estimation and comparison of different Lactation persistency methods in Tharparkar cattle - George, Linda; Gupta, Ishwar Dayal; Gupta, A K; S, Aruna T; Vineeth, M R; Achankunju, J P (Indian Journal of Dairy Science, 2021)
The present study was undertaken to estimate the various measures of lactation persistency and to estimate effect of various non-genetic factors affecting the persistency of milk production and comparison of different persistency indices using standard error as percentage of mean in Tharparkar cattle. Total 322 lactation records of 138 Tharparkar cattle were collected from Animal Genetics and Breeding Division of National Dairy and Research Institute, Karnal from 1996 to 2018 for the estimation of lactation persistency. Lactation persistency was estimated using Ratio method (P1), Prasad method (P2), Solkner and Fuchs variation method in 200 days (P3) and 305 days (P4).The least squares of means for persistency of milk yield were 149.6 ± 3.07, 0.53 ± 0.007, 1.83 ± 0.05 and 2.28 ± 0.07 in P1, P2, P3 and P4 respectively in Tharparkar cattle. Based on standard error as percentage of mean, the best method was Prasad method (1.1%). The highest values of least squares means were found for first calvers in P1 but in P3 and P4 fourth calvers were more persistent. The cows calved during rainy season were more persistent as estimated by P1 and P2 but based on P3 and P4 winter calvers were more persistent. There was a highly significant (P<0.05) positive correlation of total milk yield with all the method of persistency indices.